An overview of information literacy (Skills) in academic work / Ahmad Suffian Mohd Zahari ... [et al.] - Mohd Zahari, Ahmad Suffian; Raja Baniamin, Raja Mariam; Sekharan Nair, Gopala Kishnan; Salleh, Asri (2012)
Information literacy is becoming prevalent in educational system. It is also a vital part of universitylevel education. The emergence of information technology and later known as the information and communication technology increases the level of awareness in that particular area. Furthermore, the increasing of information in the global area had contributed to the needs of having good skills in managing information. People especially students should improve the information skills in order to become more educated in this 'information age' area. The purpose of this paper is to foresee the needs of Information Literacy (skills) in academic work. Having these abilities and skills, people can improve the knowledge and solve the problems.